SAFER Methodology: A Proposal for the Identification of Family Firms in Spain Based on the SABI Database - Casillas, José Carlos; Escribá-Esteve, Alejandro; Gómez-Miranda, María Elena; López-Fernández, María Concepción; Lorenzo-Gómez, Daniel; Requejo, Ignacio; Rojo-Ramírez, Alfonso A. (European Journal of Family Business, 2024)
Despite the fact that family firms represent a large percentage of all firms worldwide, methodological contributions regarding their estimation are very scarce. This paper offers a methodology for identifying family versus non-family firms using the SABI Informa database (Spanish version of Orbis) as a source of information, considering mainly ownership and corporate governance variables for their classification. The design of the Safer methodology allows its application without the need for massive data extraction, which contributes to its accessibility and ease of use by researchers. Furthermore, the proposed methodology has been tested using a sample of 500 companies, finding a classification error of less than five percent. This methodology has been also discussed and assumed by IEF (Instituto de la Empresa Familiar), becoming a standard in Spain. This work provides researchers with a consensus methodology for the selection of samples of family firms, which can be transferred to equivalent databases in other countries (e.g., AIDA, Italian company data or Markus in Germany), or scaled up to the Orbis database. Finally, our results also represent an advance in facilitating the work of professionals and policy makers in the development of reports on family businesses through a rigorous process of identification and classification.